PRAKTIK KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM MENGHADAPI TANTANGAN KURIKULUM DI SMK NEGERI 2 KARANGANYAR - Febrianti T. Lestari; Sukasno; Darsinah; Wafrotur Rohmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of the Merdeka Curriculum requires school principals to exercise adaptive and transformative instructional leadership. This study aims to examine the instructional leadership practices of school principals in facing curriculum implementation challenges at SMK Negeri 2 Karanganyar. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and documentation studies involving principals, vice principals, teachers, and students. Data analysis employed the Miles and Huberman model with stages of data reduction, data display, and conclusion drawing. The findings indicate that the principal implements transformational leadership focusing on teacher empowerment, curriculum knowledge enhancement, and innovative learning practice development. Challenges encountered include teacher resistance to change, limited pedagogical competence, and infrastructure constraints. Strategies developed encompass mentoring systems, learning technology optimization, strategic partnerships, and dialogic leadership involving active stakeholder participation. Effective instructional leadership proves capable of accelerating curriculum transformation despite facing organizational complexity challenges.